2021
DOI: 10.1177/0972262920983997
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Competencies and Microenterprises Sustainability

Abstract: In this article, we report a study undertaken to measure the effects of selected competency dimensions on the microenterprise sustainability in Malaysia under the premise of the resource-based view (RBV). We adopted a cross sectional approach. Quantitative data were collected from 300 micro-entrepreneurs in Malaysia who were selected using a random sampling technique. Commitment, conceptual, opportunity recognizing, organizing and relationship competencies had significant positive impacts on microenterprise su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In managing MSMEs, women must possess entrepreneurial skills, which can be acquired through various means, including openness, willingness to accept guidance, and leveraging operational support (Kim, 2023). These skills are reinforced by entrepreneurship education, understanding entrepreneurial competencies, and experience, as indicated by (Agarwal et al, 2023;Esubalew & Raghurama, 2020;Fazal et al, 2022;Laras et al, 2023;Taipale Erävala et al, 2019;Timotius, 2023):…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In managing MSMEs, women must possess entrepreneurial skills, which can be acquired through various means, including openness, willingness to accept guidance, and leveraging operational support (Kim, 2023). These skills are reinforced by entrepreneurship education, understanding entrepreneurial competencies, and experience, as indicated by (Agarwal et al, 2023;Esubalew & Raghurama, 2020;Fazal et al, 2022;Laras et al, 2023;Taipale Erävala et al, 2019;Timotius, 2023):…”
Section: Resultsmentioning
confidence: 99%
“…Entrepreneurial knowledge and skills are considered competencies (Spencer & Spencer, 1993), enabling business operators to produce optimal work output with high quality (Fazal et al, 2022). These competencies also enhance competitive advantage (Lee et al, 2022) and the long-term sustainability of businesses (Annelin & Boström, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study showed that competencies are significantly related to the economic performance of SMEs [35]. A more recent study proved that relevant competencies have significant positive effects on enterprise sustainability [36]. Hence, based on the above, we propose the following hypotheses: H 3 : Entrepreneurial competency has a significant positive effect on entrepreneurial resilience among Saudi entrepreneurs.…”
Section: Entrepreneurial Competencymentioning
confidence: 87%